ANALISA KEGAGALAN SHAFT RODA GIGI GEARBOX TYPE RFM 3090 LA 35,5/1 - Sunaryo Sunaryo; Japri Lukman; Denur Jumali (Jurnal Teknik Industri Terintegrasi, 2019)
Shaft gear is one part of the machine components that experience dynamic load will occur voltage fluctuations. When the fluctuations occur repeatedly as often as possible, there will be failure, even though the maximum voltage that occurs is still smaller than the static strength of the wheel axle material. Failure of a shaft material is inseparable from the characteristics of its structure. Failure of the shaft occurs at points where there is a voltage concentration, where the source of the stress concentration on the machine element, can be pull, groove, hole, thread, pegs and others. The weakness or failure of a SS 304 carbon steel material used as a shaft is influenced by many factors. It should be noted that the breakage of a material always begins at places where stress concentration occurs with its loading pattern. In response to the above problems, a failure analysis of the gear shaft of Stainless Steel AISI 304 is required. By testing the metal mechanical properties by tensile testing, hardness testing, obtained from fatigue test with tensile strength of 812 , 97 MPa in diameter 13 shaft of gear and 825,37 MPa for diameter 16 and yield strength of SS 304 for diameter 13 is 806,03 N / mm2 while diameter 16 equal to 821,20 N / mm2. The result of fatty test shows the three stresses given at diameter 12 (mm) of 61.2 Mpa then the resulting cycle amounted to 87476 for 145 Minutes at 2800 speed, in contrast to the fatigue test results for a given voltage of 76.5 Mpa, resulting in 87354 for 120 minutes, resulting in the greater the applied stress the cycle and time will be faster the occurrence of fatality in the material Stainless Steel AISI 304.Hardness value (Hardening) on shaft gears with Stainless Steel AISI 304 material no difference between shaft diameter 13 of HB: 133 and diameter 16 of HB: 133. The difference in diameter on the shaft does not affect the hardness value in the shaft material of the gear. Factors that affect or tend to alter the condition of fatigue or fatigue strength are the types of loading, rotation, environmental humidity (corrosion), stress concentration, temperature, material fatigue, chemical composition of materials, residual stresses.